NATURE: THE SUPREME ARTIST OF SCIENTIFIC BEAUTY BIODIVERSITY AND LIVING ART - Bandookwala, Farida Johar; Jain, Pooja (International Journal of Research -GRANTHAALAYAH, 2026)
Nature comprises of so many timeless form of beauty that in a very seamless way unites the creativity and art with high precision of scientific backup and also maintains biodiversity and ecological harmony. The laws of nature are maybe growth, adaptation, and survival, but nature has produced visually highly beautiful scenes which are also perfect in functional aspect. The landscapes, forests, and gardens, they work as the canvas of nature where different beautiful colors, textures, structures, and rhythms of birds chirping, water flowing, has evolved constantly under the influence of climate, time, and over the time as evolution. In this paper, we are going to explore the supreme artistic character of nature and examine its biodiversity, ecological organization, and principles which are backed scientifically and create living art. By summing up the perspective of aesthetic view, ecological view, philosophical view, this study is going to emphasize on the nature's beauty which is not accidental but which is interconnected in all the systems. The paper is going to highlight the ethical responsibility of conservation of nature which preserves the nature's living art for the coming generations.